IPV4 and IPV6 based hybrid approach for spam and virus detection - Hira, Swati; Ajani, Samir; Kokardikar, Pratibha; Neware, Shubhangi (International Journal of Engineering and Technology, 2018)
The proposed email setup consist of multiple mail servers distributed at two levels to achieve desirable email access performance. It is a well-established fact that 99% of the emails received over internet are either spam or contained viruses and such emails can be dropped at the first entry point of the Network. Thus, the first level in the proposed architecture has been taken as an email gateway which is equipped with antivirus and anti-spam software. Spam assassion is an open source freeware software for filtering of the spam emails. Perl based spamassassion id to CPU and Memory hungry for heavily loaded server thus this new arrangement would then overcome the Problem of slow Email access for users by detaching spamassassion from email repository servers. The second level of the servers with email repositories for users all the email servers used in this implementation would be Linux X86 servers. Virtualization technique presents a software interface to virtual machines that is similar but not identical to that of the underlying hardware. First level is implemented in Virtual machine. So as to provide scalability, portability, migration and vendor independent. Â